Occult Caries with Novel Management Technique - P. Poornima; Dhanya S. Kumar; Ashwini; N. B. Nagaveni (Research Highlights in Disease and Health Research Vol. 8, 2023)
The most common infectious disease in the world appears to be dental caries. For dentists, it might be exceedingly difficult to find occult caries or hidden carious lesions. However, it is still unknown what these lesions are, how they came to be, and why they have evaded early clinical detection. In order to gain insight into the bacteriological profile of these lesions, which may also be an etiological factor, only a very small number of microbiological studies have been done to far. This case report of occult caries includes a microbiologic study of the lesion as well as a novel strategy to managing the affected immature tooth via revascularization. The case was followed up for 6 months with vitality test eventually became positive until the root completion.